2018
DOI: 10.1038/s41592-018-0255-0
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of human cortical organoid generation

Abstract: The differentiation of pluripotent stem cells in three-dimensional cultures can recapitulate key aspects of brain development, but protocols are prone to variable results. Here we differentiated multiple human pluripotent stem cell lines for over 100 d using our previously developed approach to generate brain-region-specific organoids called cortical spheroids and, using several assays, found that spheroid generation was highly reliable and consistent. We anticipate the use of this approach for large-scale dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
369
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 373 publications
(391 citation statements)
references
References 29 publications
21
369
1
Order By: Relevance
“…Our TLS already display remarkable reproducibility both at 166 the morphological and molecular level. Nevertheless, we realize the importance of further 167 integrated comparative analysis of single TLS at single-cell resolution, such as recently 168 published for brain and kidney organoids 37,38 . Finally, in vivo somites are formed in a rhythmic 169 process involving an oscillator -the segmentation clock 39 .…”
mentioning
confidence: 98%
“…Our TLS already display remarkable reproducibility both at 166 the morphological and molecular level. Nevertheless, we realize the importance of further 167 integrated comparative analysis of single TLS at single-cell resolution, such as recently 168 published for brain and kidney organoids 37,38 . Finally, in vivo somites are formed in a rhythmic 169 process involving an oscillator -the segmentation clock 39 .…”
mentioning
confidence: 98%
“…Our optimized self-directed protocol that generates highly reproducible hCOs, complements those reported in other recent studies that use a directed patterning approach involving small molecule inhibitors and growth factors (Kadoshima, Sakaguchi et al, 2013, Velasco et al, 2019, Yoon et al, 2019. The availability of several robust platforms to produce highly similar hCOs, including the one described herein, thus allows for systematic molecular and cellular characterization of the development of the human cortex and how disease-causing mutations alter development and perhaps also homeostatic events.…”
Section: Discussionmentioning
confidence: 74%
“…Several protocols have been developed to generate cerebral organoids including both directed and self-directed (Kadoshima, Sakaguchi et al, 2013, Velasco et al, 2019, Yoon et al, 2019 and here we selected a previously established method of selfpatterned organoids (Lancaster & Knoblich, 2014a, Lancaster et al, 2013 as a starting point. Our work to standardize production revealed that optimization of the early steps of organoid generation including the embryoid body formation and neural induction phases were key in ensuring the production of similar COs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…How the mutations identified in FEZF2 allele-linked families contribute to layer organisation of the human cortex can be studied using induced Pluripotent Stem Cells (iPSCs). These pluripotent stem cells show a remarkable ability to self-organize and differentiate in vitro in three-dimensional aggregates, known as organoids or organ spheroids, and to recapitulate aspects of human brain development and function (62,63). Analysis of deep layer organization enables one to define the involvement of mutated genes discovered in patients of FEZF2 allele-linked families.…”
Section: Discussionmentioning
confidence: 99%